Rhetorical Structures of Conclusion Sections in Arabic Scholarly Articles for Indonesian and Arabic Speakers - Khoerun nisa, Salma; Rinaldi Supriadi; Tatang (IAIN Madura, 2025)
This study investigates the rhetorical structures of conclusion sections in Arabic research articles written by Arab native speakers and Indonesian scholars. Using Yang and Allison’s (2003) move-step framework and a directed content analysis approach, the study examined a balanced corpus of 80 articles from linguistics and education journals. The findings reveal that Move 2 (summary of results and evaluation) is obligatory, appearing in all texts, while Move 1 (introduction) and Move 3 (implications and recommendations) are conventional but vary in frequency. Arab authors tended to emphasize Move 3, highlighting implications and prospective contributions, whereas Indonesian authors relied more on Move 1 and Move 2, stressing restatement and summary. Linguistics articles favored Move 2, while education articles highlighted Move 3. The analysis of tense and diathesis further indicates that Arab writers used māḍī (past) to stress finality and majhūl (passive) for impersonal reporting, while Indonesian writers favored muḍāriʿ (present/future) and maʿlūm (active) for generalization and clarity. Theoretically, the study confirms the adaptability of the genre-based move-step framework across languages and disciplines. Practically, it offers pedagogical insights for teaching Arabic academic writing, emphasizing discipline-sensitive genre awareness and rhetorical flexibility